Blood pH, lactate, and ammonia following repeat sprints in trained and untrained men: Physiological responses to repeat sprints - Davis, Greggory; Perret, Jordan; Rudesill, Danielle; Bellar, David (Journal of Health and Physical Literacy, 2022)
Purpose: Examine repeat sprint performance along with blood lactate, pH, and plasma ammonia in untrained and trained men. Methods: Participants performed three 30-second Wingate cycling tests separated by five minutes each. Blood pH and lactate were measured pre-exercise and between each sprint, plasma ammonia was measured pre- and post-exercise. Each subject was classified as NO (no exercise), EO (endurance only), RO (resistance only), or RE (resistance and endurance) based upon exercise history. Results: There were significant effects for group in repeat sprint performance, as measured by peak power (Mean peak power for NO 532.88 ± 35.32; EO 607.37 ± 27.05; RO 829.01 ± 74.68; RE 731.60 ± 48.56; F = 6.75; p < 0.01) and mean power (Mean of mean power for NO 378.62 ± 34.06; EO 501.75 ± 35.31; RO 596.48 ± 45.22; RE 550.36 ± 37.51; F = 6.88; p < 0.01). No significant group differences were found for blood lactate, pH, plasma ammonia values, or fatigue index. Conclusions: Similar fatigue responses regardless of training type and that acute physiological responses to repeat sprints, including buffering of blood pH, lactate, and ammonia are not different between groups with different exercise training history.